China's public finance : reforms, challenges, and options - Lin, Shuanglin (Cambridge : Cambridge University Press, 2022)
A comprehensive, up-to-date, insightful, and innovative masterpiece on the Chinese public finance has finally emerged to fill the gap in the field. Considering China's public finance in its entirety, from tax systems, government spending, infrastructure financing, fiscal policies, local government debt, and central-local fiscal relationships to urban and rural social security and healthcare, it analyses China's public finance reforms and examines the reasons and the consequences of these reforms. It explores the challenges to China's public finance, examines its problems, and suggests potential solutions. While covering a broad range of themes, this book remains judicious with the evidence, providing its readers with innovative yet careful conclusions. Using enormous amount of the latest data and illustrative diagrams, the author explains China's public finance with expertise and clarity. This is an indispensable resource for students and scholars from a range of disciplines with an interest in the Chinese economy.
Title from publisher's bibliographic system (viewed on 28 Sep 2022).
Keywords: Finance, Public -- China; China -- Economic policy -- 2000-